Changes in liver stiffness and steatosis among patients with hepatitis C virus infection who received direct-acting antiviral therapy and achieved sustained virological response. Issue 5 (May 2018) - Kobayashi, Natsuko; Iijima, Hiroko; Tada, Toshifumi; Kumada, Takashi; Yoshida, Masahiro; Aoki, Tomoko; Nishimura, Takashi; Nakano, Chikage; Takata, Ryo; Yoh, Kazunori; Ishii, Akio; Takashima, Tomoyuki; et al.
Abstract : Aim: Whether direct-acting antiviral (DAA) therapy can reduce liver fibrosis and steatosis in patients with chronic hepatitis C virus (HCV) infection remains unclear. We evaluated sequential changes in liver stiffness and steatosis using transient elastography (TE) and the TE-based controlled attenuation parameter (CAP) in patients with HCV who received DAA therapy. Patients and methods: A total of 57 patients with HCV who received DAA therapy and achieved sustained virological response (SVR) were analyzed. Liver stiffness as evaluated with TE, steatosis as evaluated with CAP, and laboratory data were assessed before treatment (baseline), at end of treatment (EOT), 24 weeks after EOT (SVR24), and 48 weeks after EOT (SVR48). Results: Alanine aminotransferase levels, corresponding to the presence of necroinflammatory activity, significantly decreased overall, with significant differences between baseline and EOT, EOT, and SVR24, and baseline and SVR48. However, alanine aminotransferase levels showed no significant changes between SVR24 and SVR48. Median (interquartile range) liver stiffness values at baseline, EOT, SVR24, and SVR48 were 8.3 (5.0–14.8), 7.4 (4.6–14.7), 5.3 (4.1–11.8), and 5.4 (4.0–13.4) kPa, respectively (baseline vs. EOT, P =0.044; EOT vs. SVR24, P =0.011; and SVR24 vs. SVR48, P =0.054). In patients with fatty liver (CAP≥236 dB/m, n =14), CAP values at baseline and SVR48 were 253 (245–278) and 229 (209–249) dB/m, respectively ( P =0.020). Conclusion: Liver stiffness at SVR24 might reflect liver fibrosis in the patients who received DAA therapy and achieved SVR. In addition, liver steatosis reduces in the same cohort with fatty liver.